2016
DOI: 10.1134/s1067413616030176
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating asymmetry of rodent cranial structures in an industrial pollution gradient

Abstract: Fluctuating asymmetry (FA) of the mandible shape has been analyzed in bank voles from the zones affected by pollution from three copper smelters in the Urals. It has been shown that there is the necessity for a detailed analysis of the material, since the level of FA may depend on population parameters. Regardless of the pollution level, FA of the mandible region including the lower part of the mandibular body, ramus and processes is higher than in the diastema region. A gradient effect of toxic exposure on FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Landmarks (distinct locations for three dimensional measurements) chosen for FA analysis for vertebrate skulls often try to capture the whole shape of the skull (Oleksyk et al 2004;Urošević et al 2015;del Castillo et al 2016). Mandibles were chosen for digitization rather than the whole skull because past FA studies show that the greatest potential effects of contaminants are on mandible FA (Sánchez-Chardi et al 2013;Yalkovskaya et al 2016). As mentioned in Klingenberg (2015), structures that have object symmetry, like skulls, should possess single landmarks on the midline of the structure and paired landmarks on the left and right side of the structure to ensure the required data are gathered for the analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Landmarks (distinct locations for three dimensional measurements) chosen for FA analysis for vertebrate skulls often try to capture the whole shape of the skull (Oleksyk et al 2004;Urošević et al 2015;del Castillo et al 2016). Mandibles were chosen for digitization rather than the whole skull because past FA studies show that the greatest potential effects of contaminants are on mandible FA (Sánchez-Chardi et al 2013;Yalkovskaya et al 2016). As mentioned in Klingenberg (2015), structures that have object symmetry, like skulls, should possess single landmarks on the midline of the structure and paired landmarks on the left and right side of the structure to ensure the required data are gathered for the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…FA studies focus on the idea that environmental stress lowers the individual's ability to mitigate the developmental variations on each side of the organism, resulting in higher asymmetry between the two sides of an organism's structure (Klingenberg 2015). For instance, studies on small mammals reported higher levels of skull FA with increased exposure to environmental contaminants (Oleksyk et al 2004;Sánchez-Chardi et al 2013;Yalkovskaya et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory-based studies delivered important knowledge regarding relations between magnitude/pattern of variation among and within individuals and environmental [ 27 30 ] or genetic [ 18 , 31 34 ] factors, relationships between patterns of Ind and FA as evidence of whether the same developmental mechanisms generate canalization and DS [ 21 ], ontogenetic changes in magnitude of variation and covariance structure among individuals [ 23 25 , 35 – 37 ], and genetic architecture of FA [ 38 ]. Considering studies that involved specimens from wild rodent populations, the majority of them investigated associations between FA levels of meristic [ 39 , 40 ] and metric [ 41 47 ] mandibular and cranial characteristics with environmental and genetic perturbations, while few of them compared patterns between Ind and FA to infer whether developmental mechanisms behind canalization and DS are closely related [ 45 , 48 , 49 ]. Moreover, examinations of parasite (viral) infections effects on host (rodents from wild populations) morphology found that viruses can disrupt host development affecting mean cranial shape and canalization [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morphological assessment of the state of living organisms which is based on fluctuating asymmetry is one of the commonly used methods for ecological monitoring by both national and foreign scientists (Zakharov, 1987;Gileva & Kosareva, 1994;Zakharov et al, 2000;Gileva & Nokhrin, 2001;Vasil'ev, 2005;Gileva et al, 2007;Vasil'eva et al, 2003;Yalkovskaya et al, 2016;Pankakoski et al, 1992;Markowski, 1993;Graham et al, 2000;Oleksyk et al, 2004;Veličković, 2004;Vishalakshi & Singh, 2008;Allenbach, 2011;Coda et al, 2016Coda et al, , 2017Benítez et al, 2018). The assessment of the state of animal populations is essential in itself as a parameter of biodiversity (Ryadinskaya & Kokhonov, 2016).…”
Section: Introductionmentioning
confidence: 99%